Experimental behavior of double-row Y-type perfobond rib shear connectors. (November 2018) - Kim, Sang-Hyo; Han, Oneil; Kim, Kun-Soo; Park, Jun-Seung
Abstract: Although existing studies have only analyzed Y-type perfobond rib shear connectors arranged in a single row, practical applications can apply numerous such connectors to beams with narrow spaces between them. The present study aimed to evaluate the structural behavior of double-row Y-type perfobond rib shear connectors, and thus describe grouped Y-type perfobond rib shear connectors. Push-out tests were conducted in accordance with Eurocode-4, and the relative slip, shear resistance, and ductility were measured. There were two primary variables (spacing and number of Y-type perfobond rib shear connectors) and three types of test specimens: single row, double rows (120 mm spacing), and double rows (300 mm spacing). The representative single-row specimen was used to validate the push-out test results by providing a comparison with previous tests, and provided a shear resistance reference value. The other two specimen types consisted of multiple Y-type perfobond rib shear connectors attached in parallel to an H-beam. Test results revealed that shear resistance increased as the number of shear connectors increased; however, the structural behavior depended on the shear connector spacing. The specimen with wider spacing demonstrated a better ultimate load and ductility relative to the specimen with narrower spacing. Wider shear connector spacing thus leads to better structural behavior retention. Highlights: Evaluated shear behavior of double-row Y-type perfobond shear connectors Main variables were spacing and number of shear connectors. Shear resistance increases with increase in number of shear connectors. Wider spacing led to better ultimate load and ductility.